Respuesta :

mjnw
Answer is B)
When you plug 2 into the equation you have 7(2) - 3 + 4(2) = 19
14 -3+ 8= 19
11+8=19

Answer:

B) 2

Step-by-step explanation:

Alright. So you have 7x - 3 + 4x = 19.

Combine like terms, and you get 11x - 3 = 19.

If you know how to solve 2-step equations, this will be easy! I'll explain it either way though :)

1. You want to get rid of adding/subtracting first by canceling the number out. In this situation, that number is 3.

11x - 3 = 19

    + 3   + 3

11x = 22

2. Then you want to get rid of multiplying/dividing by doing the same. You want to get the variable all by itself.

11x = 22

11x/11 = 22/11

x = 2

Hope this helped! :)